Effect of a Home-Based Exercise Program on Indices of Physical Function and Quality of Life in Elderly Maintenance Hemodialysis Patients - Jonathan Myers; Khin Chan; Yu Chen; Yiming Lit; Alessandro Patti; Payam Massaband; B. Jenny Kiratli; Manju Tamura; Glenn M. Chertow; Ralph Rabkin (Karger Publishers, 2021)
Background: Patients on maintenance hemodialysis (MHD) exhibit muscle wasting and impaired physical function which can be reversed with regular exercise, but accessibility to exercise programs for this unique population is lacking. We assessed the efficacy of a home-based exercise program on a broad range of indices of physical function, quality of life (QoL), and cognitive decline in patients with MHD. Design and Methods: Twenty-eight MHD patients, mean age 66 ± 7 years, were randomized to a 12-week home-based, case-managed aerobic and resistance exercise program or to usual care (13 exercise and 15 usual care). Comparisons were made for peak VO2, ventilatory inefficiency, 6-min walk test (6MWT), 1-min sit-to-stand (1STS), muscle strength, body composition, QoL, and cognitive measures. Results: Peak VO2 improved significantly in the exercise group (p = 0.01 between groups); exercise time improved by 41 and 36% at the ventilatory threshold and peak exercise, respectively (p < 0.01 between groups), but there were no differences in ventilatory efficiency. Trends for improvements in 6MWT and 1STS in the exercise group were observed, but no differences were observed in strength or body composition. Among measures of QoL, general health determined by the SF-36 improved in the exercise group, but there were no differences between groups in cognitive function. Conclusions: MHD patients improved exercise capacity and some indices of QoL following a 12-week home-based exercise program. Home-based exercise is feasible for patients undergoing MHD and may help to obviate accessibility barriers to regular exercise.